2011
DOI: 10.1089/ars.2011.3999
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutases: Role in Redox Signaling, Vascular Function, and Diseases

Abstract: Excessive reactive oxygen species Revised abstract, especially superoxide anion (O 2 -), play important roles in the pathogenesis of many cardiovascular diseases, including hypertension and atherosclerosis. Superoxide dismutases (SODs) are the major antioxidant defense systems against O 2 -, which consist of three isoforms of SOD in mammals: the cytoplasmic Cu/ZnSOD (SOD1), the mitochondrial MnSOD (SOD2), and the extracellular Cu/ZnSOD (SOD3), all of which require catalytic metal (Cu or Mn) for their activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,099
4
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,577 publications
(1,213 citation statements)
references
References 256 publications
15
1,099
4
19
Order By: Relevance
“…Sphingosine kinase 1, which converts sphingosine to S1P, is thought to act as a switch enzyme that can affect the S1P/ceramide ratio downstream of ROS in stress signalling (Van Brocklyn & Williams, 2012). However, we found that ceramide was positively correlated with superoxide dismutase, a major antioxidant defence system against superoxide anions which cause cell stress (Fukai & Ushio‐Fukai, 2011) and negatively correlated with reactive oxygen metabolites (ROMS) in the blood. It is unclear whether bioactive ceramide had a direct effect on the level of ROMS in the blood, as measures of oxidative stress are tissue‐dependent (Xu et al ., 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Sphingosine kinase 1, which converts sphingosine to S1P, is thought to act as a switch enzyme that can affect the S1P/ceramide ratio downstream of ROS in stress signalling (Van Brocklyn & Williams, 2012). However, we found that ceramide was positively correlated with superoxide dismutase, a major antioxidant defence system against superoxide anions which cause cell stress (Fukai & Ushio‐Fukai, 2011) and negatively correlated with reactive oxygen metabolites (ROMS) in the blood. It is unclear whether bioactive ceramide had a direct effect on the level of ROMS in the blood, as measures of oxidative stress are tissue‐dependent (Xu et al ., 2014).…”
Section: Discussionmentioning
confidence: 96%
“…By contrast, depletion of SOD exacerbated hypertension. 28,29 Clinical studies confirmed that in patients with essential hypertension, blood pressure levels are positively correlated with markers of oxidative stress. 30,31 In addition, population-based observational studies demonstrated an inverse correlation between plasma antioxidant levels and blood pressure levels.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 88%
“…While copper is needed for SOD1 catalytic activity, Zn participates in proper protein folding and stability. Over 100 mutations in the human gene SOD1 are described to lead to some inherited diseases, but their mechanisms remain unclear [33].…”
Section: Superoxide Dismutase In Biological Systemsmentioning
confidence: 99%